Using multimedia-based materials in teaching speaking to elementary school students in Kabanjahe - Sofyan, Rudy; Tarigan, Bahagia (Talenta Publisher, 2019)
As the skill that usually becomes the reference of students’ success in learning English, teaching speaking needs to be given closer attention, especially in teaching English to elementary school students. Therefore, a careful choice of good approach, technique or media is required. This article aims at finding out the advantages of using multimedia-based teaching materials in teaching speaking to elementary school students in Kabanjahe, North Sumatra. This is a descriptive study taking the fifth year elementary schools students at SD Swasta Masehi in Kabanjahe of Karo Regency as the participants. The data were collected using observations and interviews. The data were analyzed qualitatively. The results of the study show that using multimedia-based materials benefits the speaking learning process in terms of increasing the students’ interest, reducing the students’ shyness, increasing students’ motivation, and promoting student-centered learning. It is concluded that using multimedia-based materials helps build elementary school students’ speaking ability.